Borrelia burgdorferi aggrecanase activity: more evidence for persistent infection in Lyme disease - Stricker, Raphael B.; Johnson, Lorraine (Frontiers in Cellular and Infection Microbiology, 2013)
Lyme disease is the most common tickborne illness in the world today. A recent study describes for the first time an enzyme produced by the spirochetal agent of Lyme disease, Borrelia burgdorferi, that cleaves aggrecan, a proteoglycan found in joints and connective tissue. Discovery of the spirochetal aggrecanase raises many questions about the pathogenesis of Lyme arthritis and lends support to the concept of persistent B. burgdorferi infection in patients with chronic Lyme disease symptoms.